The Procedure for Recognizing Liabilities in Accounting - A. Amirov (International Journal on Economics, Finance and Sustainable Development, 2022)
This article discusses the economic nature of liabilities and the procedure for recognizing them. The study clarified key issues related to the recognition of obligations and suggested ways to address them.